PENINGKATAN PRODUKTIVITAS PETERNAK SAPI POTONG DI NAGARI SARIAK LAWEH MELALUI PELATIHAN MANAJEMEN PERENCANAAN PRODUKSI YANG EFISIEN - Dwi Yuzaria; Muhammad Ikhsan Rias; Fitrimawati Fitrimawati; Fuad Madarisa; Amri Syahardi (LPPM Universitas Andalas, 2023)
This activity is conducted with cattle farmers in Nagari Sariak Laweh, Akabiluru District, Fifty Kota Regency. Based on the preliminary survey in Nagari Sariak Laweh, most cattle farmers engage in farming as a side business, alongside growing food crops. Until now, knowledge about efficient and productive livestock management among the group members remains low. Rice straw has not been utilized as feed, and farmers struggle to obtain fresh forage and afford the relatively expensive concentrate feed. Farmers also face challenges acquiring fertilizers due to the high cost of synthetic fertilizers. Therefore, the goal of this activity is to enhance the skills and knowledge of cattle farmers in the Akabiluru district regarding beef cattle management, aiming to increase the productivity of the raised beef cattle. The method of delivering the material is carried out to equip participants with good beef cattle management practices, the utilization of straw, and the use of cattle manure. The results of this activity include cattle farmers gaining an understanding and proficiency in beef cattle management. Additionally, farmers are trained to produce fermented feed and organic fertilizer. As evidence of success, participants, with the guidance of the resource persons, successfully produced 55 kg of fermented straw, 55 kg of silage, and 17 kg of organic fertilizer made from cattle manure.